2016
DOI: 10.1002/app.43809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of norbornyl modified soybean oil on CB‐filled chloroprene rubber

Abstract: Carbon black (CB)‐filled chloroprene rubber (CR) compounds and vulcanizates containing naphthenic oil (NO), soybean oil (SO), and two different levels of norbornyl modified soybean oil (MSO) were prepared and investigated. The MSO was prepared through the reaction of SO and dicyclopentadiene (DCPD) at different ratios. Various properties including gel fraction, crosslink density, bound rubber fraction, curing behavior, thermal, mechanical, and aging properties of CB‐filled CR containing different oils were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…As a consequence, the use of NSO can improve aging resistance over NO and also SO in SBR. A similar effect was also seen in the previous study …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As a consequence, the use of NSO can improve aging resistance over NO and also SO in SBR. A similar effect was also seen in the previous study …”
Section: Resultssupporting
confidence: 91%
“…With an increase of norbornylization level, the tear strength of hybrid‐filler‐filled SBR/NSO vulcanizates is increased. A similar effect was observed and discussed in our previous study . The increase in tear strength is related to a lower crosslink density and more polysulfidic crosslinks …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Since SO and NSO can be used in different rubber compounds to replace petroleum‐based plasticizers, it is desirable to explore the effect of SO and NSO in IIR compounds in comparison with NO. Our previous studies showed that SO and NSO react with various rubber additives in sulfur and metal oxide curing systems . The behavior of SO and NSO in phenolic resin curing system is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon–carbon double bonds on the norbornyl groups showed higher reactivity than those on the fatty acid chains . It was shown that NSO in rubbers, such as SBR and CR compounds, reacts with rubber additives, providing desired overall performance for rubbers, such as improved thermal stability and mechanical properties …”
Section: Introductionmentioning
confidence: 99%